ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BEHAVIORAL INTENTION APLIKASI DELIVERY SERVICE FOOD&BEVERAGE - Hayu Gathut Abyantoro Seno; Purnamaningsih Purnamaningsih (Universitas Multimedia Nusantara, 2021)
Abstract - During the Covid-19 pandemic, the food and beverage industry, especially coffee consumption, increased by 44% from 2008-2019. This is also supported by the increasing number of coffee shops with the coffee to go concept, namely coffee shops that are built with simple outlets and focus on serving take away. Fore Coffee is a coffee shop with the concept of coffee to go. During the Covid-19 pandemic, several outlets of Fore Coffee were closed. Facing this circumtance Fore Coffee focused on selling through online media, including applications. However, in 2020 data shows that the performance of the Fore Coffee app has decreased. This of course had an impact on the sales of Fore Coffee. Therefore, the aim of this research is to increase consumer desire to use the Fore Coffee application. Fourteen hypotheses will be tested in this study. The data will be analyzed by using a structural equation model (SEM). The samples analyzed were 145 samples. The results of this study indicate that time saving orientation and price saving orientation have a positive influence on post-usage usefulness and post-usage usefulness has an influence on attitude towards online food delivery services, and behavioral intention. Meanwhile, hedonic motivation and prior online purchase experience have no influence on behavioral intention. Managerial implications will be discussed in depth in this study. Keywords: Convenience; Post-Usage Usefulness; Attitude; Behavioral Intention